2019
DOI: 10.3389/fphys.2019.00997
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary Thresholds for Accelerometry-Based Mean Amplitude Deviation and Electromyography Amplitude in 7–11 Years Old Children

Abstract: We investigated the ability of energy expenditure, movement sensing, and muscle activity to discriminate sedentary and non-sedentary activities in children. Thirty-five 7–11-year-old children participated in the study. Simultaneous assessment of oxygen uptake (V̇O 2 ), triaxial accelerometry, and thigh muscle electromyography (EMG) were performed during eight different sedentary and non-sedentary activities including lying down, sitting-, standing-, and walking-related activities, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 34 publications
(64 reference statements)
0
23
0
Order By: Relevance
“…This study adds to the literature knowledge about distribution of physical activity throughout the whole intensity range among older adults. Based on the findings from the present study and from the study among children from Gao et al [32], it is necessary to further investigate especially the lower end of the intensity range and whether the previously defined cut-point to separate sedentary activities from light activities [25] is accurate among older adults.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This study adds to the literature knowledge about distribution of physical activity throughout the whole intensity range among older adults. Based on the findings from the present study and from the study among children from Gao et al [32], it is necessary to further investigate especially the lower end of the intensity range and whether the previously defined cut-point to separate sedentary activities from light activities [25] is accurate among older adults.…”
Section: Discussionmentioning
confidence: 82%
“…This may indicate that the MAD cut-points defined and validated in healthy younger adults [25,26] may have been too high in our study population. In a recent study, the optimal MAD cut-point to separate sitting from standing was suggested to be as low as 0.0033 g among children [32]. It may be that the previously defined cut-point of 0.0167 g for light-intensity activity [25] is too high among older adults.…”
Section: Discussionmentioning
confidence: 97%
“…This study was based on the laboratory phase of the Children's Physical Activity Spectrum (CHIPASE) study 35 . A total of 35 children (21 girls, 14 boys) aged 7-11 years were recruited from local schools and volunteered to participate in the study.…”
Section: Methods Participantsmentioning
confidence: 99%
“…Although participation in organized sports is mainly positively related to MC development, there may be differences between different environments [41] and countries [59]. Therefore, one should not forget the importance of outdoor play and everyday life choices [59] that help to accumulate more daily PA [60].…”
Section: Individual Correlates Of Motor Competencementioning
confidence: 99%